Genetic variability of hepatitis B virus in Uruguay: D/F, A/F genotype recombinants - López, L. (2015)
Hepatitis B virus (HBV) infection is a serious global health problem. Approximately 2 billion people worldwide have been infected, and approximately 350 million individuals currently suffer from HBV-induced chronic liver infection, which causes 600,000 deaths annually from chronic hepatitis, cirrhosis and hepatocellular carcinoma. HBV is classified in eight genotypes (A-H), and two more have been proposed (I-J). In this paper, complete genome sequences of nine Uruguayan HBV are reported. Five samples belong to genotype F1b and one to genotype A2. Three HBV recombinants were detected: A1/F1b, A2/F1b and D3/F1b. The following mutations were detected: a G1896A substitution, a 33-nucleotide deletion from position 2896 to 2928 in the Pre-S1 region involving Pre-S1 residues 3-13, a 33-nt deletion in the Pre-S1 region involving nt 2913-2945 and Pre-S1 residues 9-19. More F genotypes strains than expected were detected in this study, supporting the hypothesis that there are more people of indigenous origin than declared in our population. Also, one third of the samples analyzed were recombinants. This cannot be explained by the low HBV prevalence in Uruguay, but a high HBV infection rate in drug addicts and dialysis patients could act in favor of multiple-genotype HBV infections that could lead to recombination.